PLANETARY MAXIMA OF THE EARTH SEISMICITY - Levin B.W.; Chirkov Ye.B. (My University, 2001)
An analysis was carried out on the latitude distribution of the earthquake number and cumulative seismic energy, based on the NEIC catalogues (1900–1993). In addition to the well-known smooth maximum of the number and energy of earthquakes at the equator zone, we have discovered sharp maxima in the Earth's seismicity at neighbouring latitude zones: 30° –39° N and 0° – 9° S. Stable peaks in the latitude distribution of seismicity were picked up in the eastern and western hemispheres. Note, that local maxima in one hemisphere coincide with the local minima in another and vice versa. The possible reasons for the maxima (origin) are discussed. Among other things, new evidence revealed, several seismicity maxima which were related to certain month of the year. This is true for some regions of the Earth over the whole of the 20-year period which we studied.